2018
DOI: 10.1093/ejo/cjx093
|View full text |Cite
|
Sign up to set email alerts
|

Miniscrews failure rate in orthodontics: systematic review and meta-analysis

Abstract: Miniscrews have an acceptably low failure rate. The findings should be interpreted with caution due to high-level of heterogeneity and unbalanced groups in the included studies. High quality randomized clinical trial with large sample sizes are required to support the findings of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 72 publications
(96 reference statements)
5
63
0
1
Order By: Relevance
“…Societal costs for treatment with miniscrews would have been even higher if the success rate had been 86.5% as it was recently published in a systematic review. 18 The difference between the success rate in this trial (96%) and the systematic review might be a result from the heterogeneity of data since reviews mix data from different screw types, insertion sites and treatment concepts.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Societal costs for treatment with miniscrews would have been even higher if the success rate had been 86.5% as it was recently published in a systematic review. 18 The difference between the success rate in this trial (96%) and the systematic review might be a result from the heterogeneity of data since reviews mix data from different screw types, insertion sites and treatment concepts.…”
Section: Discussionmentioning
confidence: 84%
“…15 Inserted by orthodontists, miniscrews can be loaded and used immediately. 16,17 The failure rate is reported to be at acceptable 86.5% 18 and the experience of pain and discomfort is reported to be comparable to other orthodontic procedures. 19 A recent RCT has shown that miniscrews in comparison to molar blocks delivered significantly superior anchorage reinforcement during space closure (N. Ganzer, I. Feldmann and L. Bondemark, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 90%
“…Some included articles reported that the installation site, 21 patient age, 20,21 jaw of insertion, 14 and MI length 20 were factors associated with stability. A recent meta-analysis, 30 however, showed that MI diameter, length and design, patient age, and jaw of insertion had little effect on the failure rate. Insertion into attached gingiva was strongly related to higher success rates, whereas smoking was related to failure.…”
Section: Summary Of Evidencementioning
confidence: 98%
“…Wie viele neue Techniken tauchte sie zuerst mit Einzelfallberichten und technischen Publikationen in der Fachliteratur auf. Später wurden retrospektive Daten zu Überlebensraten in Bezug auf Implantationsstellen veröffentlicht, die zwischen 70 und 100 % lagen [25,26]. Schließlich wurden einige prospektiv angelegte klinische Studien veröffentlicht, in denen die skelettale Verankerung mit anderen Arten der konventionellen Verankerung verglichen wurde [27].…”
Section: Skelettale Verankerungunclassified